Pragmatyczne funkcje negatorów w reklamach polskich i niemieckich – próba klasyfikacji - Golonka, Joanna (Słowo. Studia językoznawcze, 2014)
Function words acquire the meaning from the context, which creates for them the environment to develop the power of influence and their persuasive potential. Expressing the speaker’s attitude towards the content, which he or she conveys, they reveal the speaker’s intentions, purposes and his or her disposition towards the recipient of the communique etc. They influence the recipient’s understanding and evaluation of the partner’s message. Thus the proper choice and the usage of the function words are significant in every kind of communication between people. The article presented displays some essential pragmatic categories, namely the role the negators play (as function words) in advertising. The examples presented come from the Polish and German languages.